Poststroke Lingual Function and Swallowing Physiology - Krekeler, Brittany N; Hopkins, Anna; Cooke, Melissa; Tabangin, Meredith; Altaye, Mekibib; Wahab, Shaun; Martin-Harris, Bonnie (Journal of speech, language, and hearing research, 2025)
Poststroke dysphagia is characterized by deficits in lingual function. However, correlations between lingual function and oral and pharyngeal swallowing impairments have not been well defined. The aim of this preliminary study was to explore if tongue pressure generative capacity in patients after ischemic stroke is associated with oropharyngeal swallowing impairments. A cross-sectional convenience sample of ischemic stroke patients underwent a videofluoroscopic swallowing study (VFSS) and completed measures of lingual function (Saliva Swallow Pressure, maximum isometric pressure [MIP], Maximum Isometric Endurance [ISO-M], and Maximum Isotonic Endurance [ISO-T]) using the Tongueometer and Iowa Oral Performance Instrument (IOPI) lingual manometry instruments. VFSS for each participant were consensus scored by two Modified Barium Swallow Impairment Profile (MBSImP)-certified raters. MBSImP Oral Total and Pharyngeal Total scores were calculated, and Swallow-by-Swallow MBSImP scores were summarized by calculating a percentage of the worst possible score across all bolus presentations for that score. Lingual measurements (swallow pressures, MIP, ISO-M, and ISO-T) were averaged across all participants, and Spearman's correlation coefficients were used to assess relationships between these lingual pressure measures and the MBSImP scores. The final sample consisted of 39 participants post-ischemic stroke (ranging from 3 months to 27 months). Average MIP was 49.6 kPA (11.25), Saliva Swallow average was 19.0 kPa (11.25), average ISO-M was 11.1 s (12.65), and average ISO-T repetitions was 30 (22.8). There were significant, moderate correlations between ISO-M and Oral Total score ( = -.41, = .0082); Component 1, Lip Closure ( = -.46, = .0026); and Component 2, Tongue Control ( = -.48, = .0016). All other correlations were nonsignificant. Isometric endurance was correlated with physiologic measures of oral swallow function. Inclusion of endurance testing in poststroke populations may add value in clinical assessment. Future studies should examine the predictive value of lingual functional measures in predicting swallow dysfunction.